2016
DOI: 10.5543/khd.2016.96158
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between healthy life style behaviors and hopelessness in patients with heart failure

Abstract: Fiziksel hastalıklarda sıklıkla hastalarda eksik olarak görülen sağlıklı yaşam biçimi davranışları bireylerde umutsuzluğa neden olabilmektedir. Bu araştırma kalp yetersizliği hastalarında sağlıklı yaşam biçimi davranışları ve umutsuzluk arasındaki ilişkiyi belirlemek amacıyla yapıldı. YÖNTEM ve GEREÇLER: Araştırmanın evrenini Turgut Özal Tıp Merkezinde Kalp Yetersizliği tanısı ile tedavi gören hastalar oluşturdu. Araştırmanın örneklemini evrenden evreni belli örnekleme yöntemiyle bulunan ve araştırmaya katılma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…It is thought that the high stress management scores of the married people may be due to the economic and social negative effects of the pandemic as a source of stress. Kılınç et al (2016) also stated in their study that married people showed higher healthy lifestyle behaviors than single ones. On the contrary, physical activity levels of single individuals were found to be better than those who were married in this study (Table 4).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is thought that the high stress management scores of the married people may be due to the economic and social negative effects of the pandemic as a source of stress. Kılınç et al (2016) also stated in their study that married people showed higher healthy lifestyle behaviors than single ones. On the contrary, physical activity levels of single individuals were found to be better than those who were married in this study (Table 4).…”
Section: Discussionmentioning
confidence: 90%
“…Göger et al (2019) found that there was no relationship between the individuals' educational status and healthy lifestyle behaviors. Kılınç et al (2016) also stated that individuals with a high level of education showed better healthy lifestyle behaviors than those with a low level of education. Similarly, in this study, it was found that those with university-undergraduate and postgraduate education, those with higher income than their expenses and those without chronic diseases led a healthier lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study on spiritual care needs by Hsiao et al ( 2011 ), 88% of patients with chronic diseases stated that having hope is important for survival. In another study, Kılınç et al ( 2016 ) reported that level of hope affected stress, physical activity and spirituality in patients with chronic diseases. In our study, in support of the literature, it was found that the relationship between the chronic disease status of the patients diagnosed with COVID-19 and their spiritual care requirement understanding and hope dimension scores was significant, and those that had a chronic disease had a higher mean score in the understanding and hope dimension ( U = 16,057.50) ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…(2011) 49-60 yaş grubundakilerin sağlıklı yaşam biçimi davranışları puanlarının yükek olduğunu, Bostan & Beşer (2017) 39 yaş ve üzerinde sağlıklı yaşam biçimi davranışları puan ortalamasının arttığını bildirmişlerdir (Bostan & Beşer, 2017;Küçükberber, Özdilli, & Yorulmaz, 2011;Sungur, Kar, Kıran & Macit, 2019) elde edilen bulgular sonucunda yaşla birlikte, kişilerin sağlık konusunda daha fazla bilgi ve deneyim sahibi olmalarına, hayat tarzlarının daha dengeli ve düzenli bir şekilde sürdürmelerine, artan kronik hastalıkların ve fonksiyonel yetersizliklerin en aza indirebilmek için sağlıklarına daha fazla önem vermeleri gibi nedenlere bağlı olarak sağlıklı yaşam farkındalığının yaşla birlikte artacağı öngörülmektedir. Araştırma bulgularımızla benzer olarak evli olan bireylerde daha yüksek sağlıklı yaşam biçimi davranışı bildiren çalışmalar bulunmaktadır (Güler, G., Güler, N., Kocataş, Yıldırım & Akgül, 2008; Kılınç, Yıldız & Kavak, 2016). Evli bireylerin bekarlara göre yaşam farkındalıklarının daha yüksek olmasının evlilerin görev ve sorumluluklarının daha fazla olmasının daha düzenli bir yaşam biçimi geliştirmelerini gerektirmesinden kaynaklandığı söylenebilir.…”
Section: Araştırmanın Etik Yönüunclassified